RANCANG BANGUN PENGONTROLAN PENGISIAN BATERAI DENGAN SUMBER SEL SURYA BERBASIS ARDUINO - Aria Nurul Haq, Saipul, Tan Suryani Sollu, Yusnaini Arifin (Foristek, 2018)
Palu is municipality located in equator where solar radiation is abundantly available. therefore, utilization of solar energy is potential. solar energy technology has some advantages, such as are of renewable energy, having no pollution an d available everywhere. recently, the use of solar energy technology, especially photovoltaic, has been used widely such as battery charger using photovoltaic. charging battery with photovoltaic as source, has been limited by instability of photovoltaic output voltage. so voltage input of battery is also fluctuated. This research applies cuk converter to increase and decrease the voltage from photovoltaic. to stabilize the output of cuk converter at 13,8 V. PID control is applied with Kp,Kd,Ki, and setpoint are 0.5, 0.25, 0.02, and 110 respectively. The result shows that use of cuk converter can raise and decrease the source voltage by regulating duty cycle, as well reduce ripple of photovoltaic voltage. the average efficiency of the cuk converter is 79 % when charge the battery. the duration time needed to charge fully the battery is 2-4 hours.